Separator for electrochemical device and electrochemical device including the same

The separation membrane for lithium secondary batteries, featuring a porous polymer substrate and a coating layer with specific binders and inorganic particles, addresses the challenge of maintaining dimensional stability at high temperatures and in wet conditions, ensuring reliable battery performance.

JP2025514268AActive Publication Date: 2025-05-02LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024563486
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-03-17
Filing Date
2024-01-25
Publication Date
2025-05-02
Estimated Expiration
2044-01-25

AI Technical Summary

Technical Problem

Existing separation membranes for lithium secondary batteries face challenges in maintaining dimensional stability at high temperatures and in wet conditions, leading to potential exposure of electrodes due to heat shrinkage.

Method used

A separation membrane comprising a porous polymer substrate with a porous coating layer containing an acrylic polymer binder, a copolymer binder with a weight average molecular weight of 40,000 to 80,000, and inorganic particles, in a weight ratio of 1:93 to 1:20, which provides improved dimensional stability under high temperature and wet conditions.

Benefits of technology

The proposed separation membrane exhibits reduced dry and wet heat shrinkage rates, preventing electrode exposure and maintaining adhesion even in wet states, thus enhancing the reliability and performance of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514268000001
    Figure 2025514268000001
  • Figure 2025514268000002
    Figure 2025514268000002
  • Figure 2025514268000003
    Figure 2025514268000003
Patent Text Reader

Abstract

The present invention relates to a separator for an electrochemical device, comprising: a porous polymer substrate; and a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer comprising an acrylic polymer binder, a copolymer binder, and inorganic particles, the copolymer binder having a weight average molecular weight of 40,000 to 80,000, and the copolymer binder and the inorganic particles being contained in a weight ratio of 1:93 to 1:20.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to Korean Patent Applications Nos. 10-2023-0035101 and 10-2023-0035102, filed with the Korean Intellectual Property Office on March 17, 2023, respectively, the contents of which are incorporated herein by reference in their entireties.

[0002] The present invention relates to a separator for an electrochemical device and an electrochemical device including the same. [Background technology]

[0003] Electrochemical elements convert chemical energy into electrical energy by utilizing electrochemical reactions, and in recent years, lithium secondary batteries have been widely used because of their high energy density, high voltage, long cycle life, and applicability in a variety of fields.

[0004] The lithium secondary battery may include an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, and may be manufactured by housing the electrode assembly in a case together with an electrolyte. The separator may include a porous coating layer including a polymer binder and inorganic particles on at least one surface of a porous substrate. The inorganic particles may be connected to other inorganic particles by the polymer binder to form an interstitial volume, and lithium ions may move through the interstitial volume. In addition to fixing the inorganic particles, the polymer binder may provide an adhesive force to the porous coating layer, and the porous coating layer may be attached to the porous substrate and the electrode, respectively.

[0005] Meanwhile, the separator must maintain stability under high temperatures and wet conditions that may occur during operation of the lithium secondary battery. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a separator for an electrochemical device having a reduced dimensional change rate in a wet state at high temperatures, a method for manufacturing the same, and an electrochemical device including the separator for an electrochemical device. [Means for solving the problem]

[0007] In one aspect of the present invention, there is provided a separator for an electrochemical device, comprising: a porous polymer substrate; and a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer comprising an acrylic polymer binder, a copolymer binder, and inorganic particles, the copolymer binder having a weight average molecular weight of about 40,000 to 80,000, and the copolymer binder and the inorganic particles being contained in a weight ratio of about 1:93 to 1:20.

[0008] The acrylic polymer binder is, for example, (meth)acrylic acid, (meth)acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, or n-ethylhexyl methacrylate. The monomer may include one or more repeating units selected from the group consisting of butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hydroxyethyl methacrylate, (meth)acrylonitrile butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate.

[0009] The copolymer binder may be a copolymer of two or more selected from the group consisting of polyacrylic acid, polyacrylamide, and polyvinyl alcohol.

[0010] The copolymer binder may be a copolymer of polyacrylic acid and polyacrylamide in a ratio of about 8:2 to 5:5.

[0011] The acrylic polymer binder may be in the form of particles having an average particle size (D50) of about 100 nm to 500 nm, and the copolymer binder may be in the form of non-particulates.

[0012] The porous coating layer may include about 90% to 95% by weight of the inorganic particles based on the total weight of the porous coating layer.

[0013] Based on the weight of the porous coating layer, the content of the acrylic polymer binder may be greater than the content of the copolymer binder.

[0014] The acrylic polymer binder and the copolymer binder may be included in a weight ratio of about 5:1 to 1.5:1.

[0015] Another aspect of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the separator being a separator for an electrochemical device having the above-described characteristics.

[0016] The electrochemical device may be a lithium secondary battery.

[0017] The electrochemical element is made of EC (ethylene The electrolyte may further include an electrolyte solution including a solvent in which EMC (ethyl methyl carbonate) / EMC (ethyl methyl carbonate) are mixed in a weight ratio of about 3 / 7.

[0018] In another aspect of the present invention, there is provided a method for manufacturing a separator for an electrochemical device, comprising forming a porous polymer substrate and a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer comprising an acrylic polymer binder, a copolymer binder and inorganic particles, the copolymer binder having a weight average molecular weight of about 40,000 to 80,000, and the copolymer binder and the inorganic particles being contained in a weight ratio of about 1:93 to 1:20.

[0019] The acrylic polymer binder is, for example, (meth)acrylic acid, (meth)acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, n-ethylhexyl meth ... The monomer may include one or more repeating units selected from the group consisting of ethylhexyl methacrylate, hydroxyethyl methacrylate, (meth)acrylonitrile butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate.

[0020] The copolymer binder may be a copolymer of two or more selected from the group consisting of polyacrylic acid, polyacrylamide, and polyvinyl alcohol.

[0021] The copolymer binder may be a copolymer of polyacrylic acid and polyacrylamide in a ratio of about 8:2 to 5:5.

[0022] The acrylic polymer binder may be in the form of particles having an average particle size (D50) of about 100 nm to 500 nm, and the copolymer binder may be in the form of non-particulates.

[0023] The porous coating layer may include about 90% to 95% by weight of the inorganic particles based on the total weight of the porous coating layer.

[0024] The content of the acrylic polymer binder may be greater than the content of the copolymer binder based on the weight of the porous coating layer.

[0025] The acrylic polymer binder and the copolymer binder may be included in a weight ratio of about 5:1 to 1.5:1.

[0026] Another aspect of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the separator being the separator for an electrochemical device according to the another aspect of the present invention.

[0027] The electrochemical device may further include an electrolyte solution containing a solvent in which EC / EMC is mixed at a weight ratio of about 3 / 7. Effect of the Invention

[0028] The separator for an electrochemical device according to the present invention can provide improved dimensional stability in a dry state and in a wet state in which the separator is immersed in an electrolyte. For example, the separator has a heat shrinkage rate of 5% or less in a dry state at a high temperature of about 200° C. or more and a heat shrinkage rate of 5% or less in a wet state at a high temperature of about 130° C. or more, and thus exposure of electrodes due to heat shrinkage of the separator can be prevented. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary knowledge in the technical field to which the present invention belongs can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.

[0030] As used herein, the term "comprising" is used in listing materials, compositions, devices, methods, etc. that are useful in the present invention, without being limited to the listed examples.

[0031] As used in this specification, the terms "about," "approximately," and "substantially" are used to mean a range or approximate value of a numerical value or degree, taking into consideration inherent manufacturing and material tolerances, and are used to prevent an infringer from unfairly exploiting the disclosure content in which precise or absolute numerical values ​​provided to aid in the understanding of the present invention are mentioned.

[0032] As used herein, "electrochemical device" may refer to a primary battery, a secondary battery, a supercapacitor, and the like.

[0033] As used herein, the term "wet state" may refer to a state in which the separator is at least partially impregnated with the electrolyte, and the term "dry state" may refer to a dry state in which the separator is not impregnated with the electrolyte.

[0034] As used herein, "durability" may refer to the property of a binder not swelling or deforming when in contact with an electrolyte, and exhibiting adhesive strength and mechanical strength as inherent physical properties.

[0035] The separator used in the lithium secondary battery is manufactured by applying a porous coating layer including a polymer binder and inorganic particles to at least one surface of a porous substrate, thereby preventing the thermal shrinkage of the porous polymer substrate, and the separator including the porous coating layer generally exhibits excellent dimensional stability in a dry state without an electrolyte. However, in a wet state in which the separator is impregnated with an electrolyte, the polymer binder may swell due to the electrolyte, or the separator may be exposed to a temperature of, for example, about 130° C. or higher during operation of the lithium secondary battery including the separator, and the adhesive strength of the polymer binder may decrease. In such a high-temperature wet state, the adhesive strength of the porous coating layer decreases, causing the separator to shrink significantly. For example, a cylindrical battery in which an electrode assembly is wound and inserted into a case under tension requires a relatively low adhesive strength between the electrodes and the separator compared to a pouch-type battery, and therefore the content of the polymer binder is low, resulting in a problem of reduced dimensional stability in a wet state.

[0036] In one embodiment of the present invention, a separator that exhibits excellent dimensional stability under high temperature and wet conditions is provided while maintaining a relatively low content of polymer binder in the porous coating layer.

[0037] According to one embodiment of the present invention, there is provided a separator for an electrochemical device, comprising: a porous polymer substrate; and a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer comprising an acrylic polymer binder, a copolymer binder, and inorganic particles, the copolymer binder having a weight average molecular weight of about 40,000 to 80,000, and the copolymer binder and the inorganic particles being contained in a weight ratio of about 1:93 to 1:20.

[0038] The porous polymer substrate may be a porous membrane having a plurality of pores formed therein, and may electrically insulate the positive and negative electrodes of an electrochemical device to prevent short circuiting. For example, when the electrochemical device is a lithium secondary battery, the separator made of the porous polymer substrate may be an ion-conductive barrier that blocks electrical contact between the positive and negative electrodes while allowing lithium ions to pass through. At least a portion of the pores may form a three-dimensional network that communicates with the surface and the interior of the porous polymer substrate, and a fluid may pass through the porous polymer substrate through the pores.

[0039] The porous polymer substrate may be made of a material that is physically and chemically stable against the electrolyte, which is an organic solvent. For example, the porous polymer substrate may include, but is not limited to, polyolefins such as polyethylene, polypropylene, and polybutylene, polyvinyl chloride, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, nylon, polytetrafluoroethylene, and copolymers or mixtures thereof. For example, a polyolefin resin may be used as the porous polymer substrate. Polyolefin resins can be processed to a relatively thin thickness and are easy to apply a coating slurry, making them suitable for manufacturing electrochemical devices with higher energy density.

[0040] The porous polymer substrate may have a single layer or a multi-layer structure. The porous polymer substrate may include two or more polymer resin layers having different melting points (Tm) and may provide a shutdown function during high-temperature runaway of the battery. For example, the porous polymer substrate may include a polypropylene layer having a relatively high melting point and a polyethylene layer having a relatively low melting point. For example, the porous polymer substrate may have a three-layer structure in which polypropylene, polyethylene, and polypropylene are laminated in this order. The polyethylene layer may shut down the pores while melting as the temperature of the battery rises above a predetermined temperature, thereby preventing thermal runaway of the battery.

[0041] The thickness of the porous polymer substrate may be about 1 μm to 100 μm. For example, the thickness of the porous polymer substrate may be about 10 μm to 90 μm, 20 μm to 80 μm, 30 μm to 70 μm, or 40 μm to 60 μm. For example, the thickness of the porous polymer substrate may be about 1 μm to 30 μm. Or, the thickness of the porous polymer substrate may be about 5 μm to 15 μm, or about 8 μm to 13 μm. By controlling the thickness of the porous polymer substrate within the above range, the separator manufactured using the porous polymer substrate can minimize the volume of the electrochemical device and increase the amount of active material contained in the electrochemical device while electrically insulating the positive and negative electrodes of the electrochemical device.

[0042] The porous polymer substrate may include pores having an average diameter of about 0.01 μm to 1 μm. For example, the diameter of the pores in the porous polymer substrate may be about 0.01 μm to 0.09 μm, 0.02 μm to 0.08 μm, 0.03 μm to 0.07 μm, or 0.04 μm to 0.06 μm. Alternatively, the size of the pores may be about 0.02 μm to 0.06 μm. By adjusting the size of the pores in the porous polymer substrate within the above ranges, the air permeability and ion conductivity of the entire separation membrane to be manufactured can be adjusted.

[0043] In one embodiment, the porous polymer substrate may have an air permeability of about 10s / 100cc to 100s / 100cc. For example, the air permeability of the porous polymer substrate may be about 10s / 100cc to 90s / 100cc, 20s / 100cc to 80s / 100cc, 30s / 100cc to 70s / 100cc, or 40s / 100cc to 60s / 100cc. Alternatively, the air permeability of the porous polymer substrate may be about 50s / 100cc to 70s / 100cc. When the air permeability of the porous polymer substrate is within the above range, the air permeability of the separator to be manufactured may be provided within a range suitable for ensuring the output and cycle characteristics of the electrochemical device.

[0044] Meanwhile, the air permeability (s / 100cc) means the time (seconds) required for 100cc of air to pass through a porous polymer substrate or a separation membrane having a predetermined area under a certain pressure. The air permeability is measured according to ASTM The densitometer can be used to measure the air permeability in accordance with ASTM D 726-58, ASTM D726-94, or JIS-P8117. For example, a Gurley 4110N instrument is used, which is measured using air at a pressure of 0.304 kPa and a densitometer of 1.215 kN / m 2 Under water pressure of 100cc of air, 1 square inch (or 6.54cm 2 For example, the time it takes for 100cc of air to pass through a 1 inch2 sample at room temperature under a constant pressure of 4.8 inches of water can be measured using the Asahi Seiko EG01-55-1MR.

[0045] The porous polymer substrate may have a porosity of about 10 vol% to 60 vol%. For example, the porosity of the porous polymer substrate may be about 15 vol% to 55 vol%, 20 vol% to 50 vol%, 25 vol% to 45 vol%, or 30 vol% to 40 vol%. Alternatively, the porosity of the porous polymer substrate may be about 30 vol% to 50 vol%. When the porosity of the porous polymer substrate is within the above range, the ionic conductivity of the separator produced may be provided within a range suitable for ensuring the output and cycle characteristics of an electrochemical device.

[0046] The porosity means a ratio of the volume of pores to the total volume of a porous polymer substrate. The porosity can be measured by a method known in the art. For example, the porosity can be measured by BET (Brunauer Electron Transfer Assay) using nitrogen gas adsorption. It can be measured by the Emmett Teller method, the capillary flow porometer, water or mercury penetration methods.

[0047] The porous coating layer is formed on at least one surface of the porous polymer substrate and may include an acrylic polymer binder, a copolymer binder, and inorganic particles.

[0048] The porous coating layer may be formed by coating at least one surface of a porous polymer substrate with a coating slurry including an acrylic polymer binder, a copolymer binder, inorganic particles, and a dispersion medium. For example, the separator may be manufactured by applying the coating slurry to at least one surface of a porous polymer substrate and then drying the coating slurry to remove the dispersion medium. The porous coating layer includes an interstitial volume in which the inorganic particles are connected by the acrylic polymer binder and the copolymer binder, and adheres to the porous polymer substrate while allowing lithium ions to pass therethrough, thereby preventing thermal shrinkage of the porous polymer substrate.

[0049] The coating slurry includes a dispersion medium, and can dissolve or disperse at least a portion of the acrylic polymer binder or the copolymer binder, and can disperse inorganic particles. The coating slurry can be used in which the polymer binder and inorganic particles are uniformly dispersed by adjusting the type and content of the dispersion medium. For example, the dispersion medium can be one selected from the group consisting of water, ethanol, acetone, isopropyl alcohol (IPA), dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), acetonitrile, and combinations thereof. In one embodiment, the dispersion medium can be water. Using the above-mentioned types of dispersion medium, a porous coating layer in which inorganic particles are uniformly dispersed can be formed.

[0050] The coating slurry may have a viscosity of about 100 cps to about 1,000 cps. For example, the viscosity of the coating slurry may be about 200 cps to about 900 cps, 300 cps to about 800 cps, 400 cps to about 700 cps, or 500 cps to about 600 cps. Or, the viscosity of the coating slurry may be about 300 cps to about 800 cps.

[0051] The coating slurry may further include additives such as a dispersant, a surfactant, an antifoaming agent, a flame retardant, and a wetting agent to improve dispersibility and flame retardancy, and to improve the uniformity of the porous coating layer formed. For example, the dispersant may include one or more selected from the group consisting of oil-soluble polyamines, oil-soluble amine compounds, fatty acids, fatty alcohols, sorbitan fatty acid esters, tannic acid, pyrogallic acid, and polyacrylic acid. The above-mentioned types of dispersants may be used to improve the stability of the coating slurry, and ensure the uniformity of the porous coating layer formed from the coating slurry.

[0052] The additive may be included in an amount of about 0 to 5 wt % based on the total weight of the coating slurry. For example, the additive may be included in an amount of about 0.01 to 4 wt %, 0.1 to 3 wt %, or 1 to 2 wt %. Alternatively, the additive may be included in an amount of about 3 to 5 wt %. By adjusting the additive content within the above range, uniform dispersion and stability of inorganic particles included in the coating slurry can be achieved.

[0053] The dispersion medium contained in the coating slurry may be removed by drying or heating after the porous coating layer is formed. For example, the porous coating layer may contain about 5 ppm or less of the dispersion medium. In one embodiment, the porous coating layer may be composed of an acrylic polymer binder, a copolymer binder, and inorganic particles. In the process of removing the dispersion medium, a plurality of pores may be formed on the surface and inside of the porous coating layer. The pores may include interstitial volumes formed between inorganic particles, and may have a structure that forms a three-dimensional network to allow fluid to pass through.

[0054] The thickness of the porous coating layer may be about 1 μm to 15 μm. For example, the thickness of the porous coating layer may be about 2 μm to 14 μm, 3 μm to 13 μm, 4 μm to 12 μm, 5 μm to 11 μm, 6 μm to 10 μm, or 7 μm to 9 μm. Alternatively, the thickness of the porous coating layer may be about 1 μm to 5 μm. By controlling the thickness of the porous coating layer within the above range, it is possible to minimize the shrinkage of the porous polymer substrate and realize stable adhesion to the porous polymer substrate.

[0055] The acrylic polymer binder can bind inorganic particles and the like contained in the porous coating layer, and can impart adhesive strength to the porous coating layer. The acrylic polymer binder can be selected from the group consisting of (meth)acrylic acid, (meth)acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, and n-ethylhexyl methacrylate. The monomer may include one or more repeating units selected from the group consisting of butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hydroxyethyl methacrylate, (meth)acrylonitrile butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate.

[0056] For example, the acrylic polymer binder may include one or more selected from the group consisting of polyacrylic acid, methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, ethylhexyl acrylate, methyl methacrylate, styrene-butadiene rubber, nitrile-butadiene rubber, acrylonitrile-butadiene rubber, and acrylonitrile-butadiene-styrene rubber.

[0057] The acrylic polymer binder may be in a particle shape. For example, the acrylic polymer binder may be spherical or elliptical, but is not limited thereto. The acrylic polymer binder may have an average particle size (D50) of about 100 nm to 500 nm. For example, the acrylic polymer binder may have an average particle size (D50) of about 150 nm to 450 nm, 200 nm to 400 nm, or 250 nm to 350 nm. Alternatively, the acrylic polymer binder may be spherical particles having an average particle size (D50) of about 250 nm to 400 nm. By controlling the particle size of the acrylic polymer binder particles within the above range, it is possible to simultaneously ensure the migration path of lithium ions and the adhesive strength of the porous coating layer to the porous polymer substrate.

[0058] The acrylic polymer binder may contribute to exhibiting a dry adhesive strength, which is an adhesive strength of the porous coating layer in a dry state, and the copolymer binder may contribute to exhibiting a wet adhesive strength, which is an adhesive strength of the porous coating layer in a wet state. The copolymer binder may be physically or chemically stable in an electrolyte solution compared to the acrylic polymer binder, and may not lose adhesive strength even in a wet state, thereby maintaining the adhesion of the porous coating layer to the porous polymer substrate in a wet state and reducing thermal shrinkage of the porous polymer substrate.

[0059] The copolymer binder may be a copolymer of two or more selected from the group consisting of polyacrylic acid (PAA), polyacrylamide (PAM), and polyvinyl alcohol (PVA). For example, the copolymer binder may be a random copolymer of two or more selected from the group consisting of polyacrylic acid, polyacrylamide, and polyvinyl alcohol. In one embodiment, the copolymer binder may be a copolymer of polyacrylic acid and polyacrylamide. In the copolymer binder, the polyacrylic acid exhibits durability against an electrolyte and can form bonds between inorganic particles, etc. The polyacrylamide exhibits a higher modulus value than the polyacrylic acid, and can further improve the durability of the copolymer binder against an electrolyte and can maintain the shape of the copolymer binder even in an electrolyte.

[0060] When the copolymer binder is a copolymer of polyacrylic acid and polyacrylamide, the copolymer binder may be a copolymer of polyacrylic acid and polyacrylamide at a ratio of about 8:2 to 5:5. For example, the copolymer binder may be a copolymer of polyacrylic acid and polyacrylamide at a ratio of about 8:2, 7:3, 6:4, or 5:5. Alternatively, the copolymer binder may be a copolymer of polyacrylic acid and polyacrylamide at a ratio of about 7:3 to 5:5. By copolymerizing polyacrylic acid and polyacrylamide at the above ratio, durability against an electrolyte can be ensured while ensuring interstitial volume due to binding of inorganic particles, etc. contained in the porous coating layer.

[0061] Meanwhile, the copolymer binder may be in a non-particulate shape. The non-particulate shape may collectively mean an irregular shape other than a spherical or elliptical shape. The non-particulate copolymer binder may form bonds between inorganic particles and between inorganic particles and the acrylic polymer particles, thereby imparting adhesive strength to the porous coating layer.

[0062] In addition, the weight average molecular weight (Mw) of the copolymer binder may be about 40,000 to 80,000. For example, the weight average molecular weight of the copolymer binder may be about 45,000 to 75,000, 50,000 to 70,000, or 55,000 to 65,000. Alternatively, the weight average molecular weight of the copolymer binder may be about 60,000 to 70,000. By controlling the weight average molecular weight of the copolymer binder within the above range and providing a coating slurry viscosity not exceeding 1000 cps, it is possible to prevent structural deformation of the copolymer binder due to the electrolyte and reduce the thermal shrinkage rate of the separator in a wet state.

[0063] The weight average molecular weight of the copolymer binder was determined by gel permeation chromatography (GPC). The weight average molecular weight can be measured by PL Olexis (Polymer Chromatography, PL GPC220, Agilent Technologies). The measurement can be performed using an Agilent High Temperature RI detector under the conditions of a sample concentration of 1.0 mg / mL, a flow rate of 1.0 mL / min, and an injection volume of 200 μL (corrected with a cubic function, standard: Polystyrene) using TCB (Trichlorobenzene) as the solvent in a column of Agilent Laboratories (column temperature: 160°C).

[0064] The copolymer binder and the inorganic particles may be included in a weight ratio of about 1:93 to 1:20. For example, the weight ratio of the copolymer binder and the inorganic particles may be 1:93, 1:92, 1:91, 1:90, 1:85, 1:80, 1:75, 1:70, 1:65, 1:60, 1:55, 1:50, 1:45, 1:40, 1:35, 1:30, 1:25, or 1:20. Alternatively, the weight ratio of the copolymer binder and the inorganic particles may be about 1:93 to 1:46. Within the above range, a separator suitable for a cylindrical battery can be manufactured that has reduced thermal shrinkage due to the maintenance of adhesive strength in a wet state.

[0065] Based on the total weight of the porous coating layer, the content of the acrylic polymer binder may be greater than the content of the copolymer binder. The weight ratio of the acrylic polymer binder to the copolymer binder may be about 5:1 to 1.5:1. For example, the weight ratio of the acrylic polymer binder to the copolymer binder may be about 5:1, 4.5:1, 4:1, 4:1, 3.5:1, 3:1, 2.5:1, 2:1, or 1.5:1. By adjusting the content of the binder, etc. within the above range, a separator suitable for a cylindrical battery can be manufactured with reduced thermal shrinkage in both a dry state and a wet state.

[0066] The inorganic particles may be electrochemically stable. The inorganic particles may be within the operating voltage range of the electrochemical element (e.g., Li / Li + There are no particular limitations on the inorganic particles as long as they do not undergo oxidation and / or reduction reactions at a voltage of 0 to 5 V relative to the electrolyte. For example, when inorganic particles with a high dielectric constant are used as the inorganic particles, they can contribute to an increase in the degree of dissociation of an electrolyte salt, such as a lithium salt, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte. For the reasons described above, the inorganic particles may include inorganic particles with a high dielectric constant having a dielectric constant of about 5 or more, for example, about 10 or more. Non-limiting examples of inorganic particles with a dielectric constant of about 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, Al(OH)3, SiC, AlOOH, TiO2 or mixtures thereof.

[0067] In addition, as the inorganic particles, inorganic particles having lithium ion conduction ability, that is, those containing lithium element but not storing lithium and having a function of moving lithium ions can be used. Non-limiting examples of inorganic particles having lithium ion conduction ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate such as Li 3.25 Ge 0.25 P 0.75 S4 (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 - based glass such as Li3PO4 - Li2S - SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 - based glass such as LiI - Li2S - P2S5 (Li x P y S z (PO4)3, 0 < x < 3, 0 < y < 3, 0 < z < 7) or mixtures thereof, and the like.

[0068] In addition, the inorganic particles may be flame-retardant inorganic particles that can impart flame retardancy to the separator or prevent a sudden rise in temperature inside the electrochemical device. Non-limiting examples of flame-retardant inorganic particles include Sb2O3, Sb2O4, Sb2O5, SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, SiO2, Al2O3, AlOOH, Al(OH)3, SiC, TiO2, H3BO3, HBO2, and mixtures thereof.

[0069] The average particle size (D50) of the inorganic particles may be about 50 nm to 5,000 nm. For example, the average particle size (D50) of the inorganic particles may be about 100 nm to 4,500 nm, 200 nm to 4,000 nm, 300 nm to 3,000 nm, 400 nm to 2,000 nm, or 500 nm to 1,000 nm. If the average particle size of the inorganic particles is less than about 50 nm, the specific surface area increases, and a polymer binder is further required for bonding between the inorganic particles, which is disadvantageous in terms of electrical resistance. If the average particle size of the inorganic particles exceeds about 5,000 nm, the uniformity of the coating layer surface decreases, which may cause damage to the porous polymer substrate or electrode during lamination.

[0070] In addition, the aspect ratio of the inorganic particles may be about 1 to 2. For example, the aspect ratio of the inorganic particles may be about 1.1 to 1.9, 1.2 to 1.8, 1.3 to 1.7, or 1.4 to 1.6. By controlling the aspect ratio of the inorganic particles within the above range, the polymer binder can be easily moved through the voids between the inorganic particles, and ultimately, a porous coating layer including an interstitial volume through which lithium ions can move can be formed.

[0071] The BET (Brunauer-Emmett-Teller) specific surface area of ​​the inorganic particles is about 5 m 2 / g or more 25m 2For example, the BET specific surface area of ​​the inorganic particles may be about 6 m 2 / g or more 24m 2 / g or less, 7m 2 / g or more 23m 2 / g or less, 8m 2 / g or more 22m 2 / g or less, 9m 2 / g or more 21m 2 / g or less, 10m 2 / g or more 20m 2 / g or less, 11m 2 / g or more 19m 2 / g or less, 12m 2 / g or more 18m 2 / g or less, 13m 2 / g or more 17m 2 / g or less, or 14m 2 / g or more 26m 2 / g or less. By adjusting the BET specific surface area of ​​the inorganic particles within the above range, the movement of the polymer binder through the voids between the inorganic particles can be adjusted.

[0072] The porous coating layer may contain about 90 wt% to 95 wt% of the inorganic particles, based on the total weight of the porous coating layer. For example, the porous coating layer may contain about 90 wt% to 95 wt%, 91 wt% to 92 wt%, or 93 wt% to 94 wt% of the inorganic particles. Alternatively, the porous coating layer may contain about 92 wt% to 94 wt% of the inorganic particles. By adjusting the content of the inorganic particles within the above ranges, a separator having mechanical strength and thermal properties suitable for a cylindrical battery can be manufactured.

[0073] In the separation membrane, the loading amount of the porous coating layer relative to the area of ​​the porous polymer substrate is about 1.0 g / m 2 More than 6.0g / m 2 For example, the loading of the porous coating layer can be about 1.5 g / m 2 More than 5.5g / m 2 Below 2.0g / m 2 More than 5.0g / m 2 Below 2.5g / m2 More than 4.5g / m 2 Less than or equal to 3.0 g / m 2 More than 4.0g / m 2 In one embodiment, the loading of the porous coating layer can be about 5.5 g / m 2 More than 6.0g / m 2 By adjusting the loading amount of the porous coating layer within the above range, the durability of the separator against the electrolyte can be ensured.

[0074] The separator for an electrochemical device may have an air permeability of about 50s / 100cc to 150s / 100cc. For example, the air permeability of the separator may be about 60s / 100cc to 140s / 100cc, 70s / 100cc to 130s / 100cc, 80s / 100cc to 120s / 100cc, or 90s / 100cc to 110s / 100cc. In one embodiment, the air permeability of the separator may be about 100s / 100cc to 120s / 100cc. When the air permeability of the separator is within the above range, the output, stability, and cycle characteristics of the electrochemical device can be ensured.

[0075] Meanwhile, the separator for an electrochemical device may have a heat shrinkage of about 10% or less. For example, the separator may have a heat shrinkage of about 5% or less in a dry state, and a heat shrinkage of about 10% or less in a wet state. In one embodiment, the separator may have a heat shrinkage of about 200° C. in a dry state for 30 minutes, and a heat shrinkage of about 10% or less in a wet state for 30 minutes, based on the dimensional change when the separator is exposed to 135° C. while being immersed in an electrolyte. In one embodiment, the heat shrinkage of about 5% or less in a dry state, and a heat shrinkage of about 5% or less in a wet state.

[0076] When a secondary battery cell is manufactured using the separator for an electrochemical device, the secondary battery cell may have an electrical resistance of about 0.5 Ohm to 1.5 Ohm. For example, the electrical resistance of the secondary battery cell may be about 0.6 Ohm to 1.4 Ohm, 0.7 Ohm to 1.3 Ohm, 0.8 Ohm to 1.2 Ohm, or 0.9 Ohm to 1.1 Ohm. In one embodiment, the electrical resistance of the secondary battery cell may be about 0.6 Ohm to 0.8 Ohm.

[0077] Another embodiment of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being the separator for an electrochemical device according to the embodiment described above. The electrochemical device may be manufactured by inserting an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode into a case or pouch and sealing the case or pouch. Before sealing the case or pouch, an electrolyte may be injected to immerse the electrode assembly in the electrolyte. The shape of the case or pouch is not limited. For example, the electrochemical device may be a cylindrical, square, coin, or pouch-shaped lithium secondary battery.

[0078] The positive electrode and the negative electrode may be coated by applying and drying an electrode active material to at least one surface of each current collector. The current collector may be a material that is conductive without inducing a chemical change in the electrochemical device. For example, the positive electrode current collector may be, but is not limited to, aluminum, nickel, titanium, calcined carbon, stainless steel, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, or the like. For example, the negative electrode current collector may be, but is not limited to, copper, nickel, titanium, calcined carbon, stainless steel, or copper or stainless steel surface treated with carbon, nickel, titanium, silver, or the like. The current collector may be in various forms such as a metal sheet, a film, a foil, a net, a porous body, a foam, or the like.

[0079] The positive electrode comprises a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. The positive electrode active material includes layered compounds such as lithium manganese composite oxides (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and compounds substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; chemical formula LiNi 1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3), Ni-site type lithium nickel oxides represented by this formula; chemical formula LiMn 1-x M x O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or lithium manganese composite oxides represented by Li2Mn3MO8 (where M = Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the chemical formula Li is substituted with alkaline earth metal ions; disulfide compounds; one or a mixture of two or more of Fe2(MoO4)3 may be included.

[0080] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. As the negative electrode active material, the negative electrode includes carbon such as lithium metal oxides, graphitizable carbon, graphite-based carbon; LixFe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Si, SiO x (0 < x < 2), silicon-based materials such as SiC, Si alloys; Sn x Me 1-x Me’ y O z(Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), etc. metal composite oxides; lithium metal; lithium alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; one or more mixtures selected from titanium oxide may be included.

[0081] The conductive material may be any one selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, carbon nanotube, activated carbon, and polyphenylene derivative, or a mixture of two or more of these conductive materials. The carbon nanotube has a cylindrical form with a nanosize diameter of a graphite sheet and has an sp bonding structure, and exhibits conductor or semiconductor characteristics depending on the angle and structure of the graphite sheet being wound. Carbon nanotubes can be classified into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT) according to the number of bonds forming the wall, and these carbon nanotubes can be appropriately selected according to the use of the dispersion. For example, it may be any one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more of these conductive materials.

[0082] ​​​​​​ The binder resin may be a binder resin commonly used in electrodes of electrochemical devices. Non-limiting examples of the binder resin include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, and polyvinylidene fluoride-co-hexafluoropropylene. fluoride-cotrichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate acetate), cellulose acetate butyrate, cellulose acetate propionate acetatepropionate, cyanoethyl pullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan and carboxyl methylcellulose. Examples of suitable cellulose acetate preparations include, but are not limited to, methyl cellulose.

[0083] The electrolyte is A + B - A salt having the structure:+ Li + , Na + , K + or a combination thereof, such as B - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a salt containing an anion such as these or a combination thereof may be dissolved or dissociated in an organic solvent such as propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.

[0084] For example, the electrolyte may include a solvent with a weight ratio of EC / EMC of about 3 / 7, which may maximize dimensional stability of the separator according to this embodiment.

[0085] The electrochemical device including the electrode assembly may be a lithium secondary battery. The battery may be used as a unit cell, and may be used as a battery module including the unit cell, a battery pack including the battery module, or a device including the battery pack as a power source. Examples of the device include computers, mobile phones, power tools, etc. Small devices such as electric tools and electric vehicles (EVs) and hybrid electric vehicles (Hybrid Electric Vehicle (HEV), Plug-in Hybrid Electric Examples of electric vehicles include electric vehicles (PHEVs, PHEVs, etc.); electric two-wheeled vehicles (E-bikes, E-scooters, etc.); electric golf carts; and medium- to large-sized devices such as power storage systems, but are not limited to these.

[0086] According to another embodiment of the present invention, there is provided a method for manufacturing a separator for an electrochemical device, the method comprising the steps of: forming a porous coating layer, the porous coating layer including an acrylic polymer binder, a copolymer binder, and inorganic particles, on at least one surface of a porous polymer substrate. The same contents as those described in the above embodiment of the separator for an electrochemical device are substituted for those described in the above embodiment.

[0087] The step of forming the porous coating layer may include preparing a coating slurry including an acrylic polymer binder, a copolymer binder, inorganic particles, and a dispersion medium, and applying the coating slurry to the porous polymer substrate and drying the coating slurry.

[0088] The step of forming the porous coating layer may further include a step of subjecting at least one surface of the porous polymer substrate to a corona discharge treatment before applying the coating slurry to the porous polymer substrate. The step of subjecting at least one surface of the porous polymer substrate to a corona discharge treatment may prevent a decrease in the adhesive strength between the surface of the porous polymer substrate and the surface of the porous coating layer at a high temperature higher than a predetermined temperature, and may prevent an electrolyte from causing a decrease in the adhesive strength between the surface of the porous polymer substrate and the surface of the porous coating layer.

[0089] The corona discharge treatment may be performed by treating at least one surface of the porous polymeric substrate in air at a voltage of about 0.1 kV to 10 kV. For example, the corona discharge treatment may be performed in air at a voltage of about 0.2 kV to 9 kV, 0.3 kV to 8 kV, 0.4 kV to 7 kV, 0.5 kV to 6 kV, 0.6 kV to 5 kV, 0.7 kV to 4 kV, 0.8 kV to 3 kV, 0.9 kV to 2 kV, or 1.0 kV to 2 kV. In one embodiment, the corona discharge treatment may be performed in air at a voltage of about 1.8 kV. By adjusting the applied voltage of the corona discharge treatment within the above range, an appropriate number of functional groups can be formed on the surface of the polymeric substrate, and damage to the surface of the polymeric substrate can be prevented.

[0090] The step of forming the porous coating layer may include applying the coating slurry to the porous polymer substrate to coat it. For example, the coating may be formed by a method such as, but not limited to, a bar coater, a wire bar coater, a roll coater, a spray coater, a spin coater, an inkjet coater, a screen coater, a reverse coater, a gravure coater, a knife coater, a slot die coater, a hot melt coater, a comma coater, a direct metering coater, etc. In one embodiment, the step of forming the porous coating layer may be simultaneously coating the coating slurry on both sides of the porous polymer substrate using a bar coater or a slot die coater.

[0091] The step of forming the porous coating layer may include applying the coating slurry to a porous polymer substrate, and then drying or heating the porous coating layer to evaporate the dispersion medium contained in the porous coating layer. The removal of the dispersion medium may be performed at a temperature that can evaporate only the dispersion medium contained in the porous coating layer without deforming the polymer binder contained in the porous coating layer. For example, the removal of the dispersion medium may be performed by heating the porous coating layer to a predetermined temperature, and the temperature of the surface of the porous coating layer does not exceed 60° C. When the porous coating layer is heated under the above conditions, the thermal energy may be used first to heat the dispersion medium to cause a phase change, and not to deform the polymer binder.

[0092] The present invention will be described in more detail below with reference to examples and experimental examples. The following examples and experimental examples are provided to illustrate the present invention, and the present invention is not limited to the following examples and experimental examples.

[0093] Example 1 Coating slurry preparation At room temperature (25℃), 2.77g (11.4% solids) of a copolymer of polyacrylic acid and polyacrylamide (weight average molecular weight: 70,000, pH 7.2, viscosity 55cps@RT) as a copolymer binder, 30g of Al2O3 (particle size (D50): 500nm) as inorganic particles, and 3.1g (25% solids) of a PAA-based polymer dispersant as an additive were added to 53.7mL of distilled water, and stirred for 120 minutes with a shaker. Then, 2.42g (40% solids) of an acrylic polymer binder (particle size (D50): 150nm, Tg: -25℃) and 0.19g (100% solids) of a wetting agent as an additive were added to produce a coating slurry in which the copolymer binder and inorganic particles are dispersed.

[0094] Preparation of porous polymer substrates As the porous polymer substrate, a polyethylene film having a size of 20 cm×30 cm and a thickness of 10 μm (MI: 0.2 g / 10 min, Tm: 135° C., porosity: 45%, average pore size: 35 nm) was used.

[0095] Separation membrane manufacturing The coating slurry was coated on both sides of a polyethylene film using a bar coater to form a coating layer with a thickness of 1.5 μm.

[0096] The process of applying low-temperature airflow to the polyethylene film with the coating layer and removing the dispersion medium was repeated five times to produce a separator with a total thickness of 13 μm and a weight ratio of acrylic polymer binder, copolymer binder, additives, and inorganic particles contained in the porous coating layer of 3:1:3:93.

[0097] Although the order of steps in the method for producing a separation membrane of the present invention has been described above, the order of steps may be appropriately modified and adjusted as necessary, for example, the step of preparing a porous substrate may be performed prior to the step of preparing a coating slurry, or both steps may be performed simultaneously.

[0098] Example 2 A separator was manufactured in the same manner as in Example 1, except that the copolymer binder having a weight average molecular weight of 67,000 was used in preparing the coating slurry.

[0099] Example 3 A separator (the weight ratio of the acrylic polymer binder, the copolymer binder, the additive, and the inorganic particles contained in the porous coating layer was 3:2:3:92) was prepared in the same manner as in Example 1, except that the coating slurry was prepared by adding 2.45 g of the acrylic polymer binder, 5.6 g of the copolymer binder, 30 g of the inorganic particles, 3.13 g of the dispersant, and 0.2 g of the wetting agent.

[0100] Example 4 A separator was manufactured in the same manner as in Example 1, except that in preparing the coating slurry, a copolymer binder obtained by polymerizing polyacrylic acid and polyacrylamide in a ratio of 7:3 was used.

[0101] Comparative Example 1 A separator was manufactured in the same manner as in Example 1, except that the copolymer binder having a weight average molecular weight of 35,000 was used in preparing the coating slurry.

[0102] Comparative Example 2 A separator was manufactured in the same manner as in Example 1, except that the copolymer binder having a weight average molecular weight of 100,000 was used in preparing the coating slurry.

[0103] Comparative Example 3 A separator was manufactured in the same manner as in Example 1, except that the copolymer binder having a weight average molecular weight of 160,000 was used in preparing the coating slurry.

[0104] Comparative Example 4 A separator (the weight ratio of the acrylic polymer binder, the copolymer binder, the additive, and the inorganic particles contained in the porous coating layer was 3:0:3:94) was prepared in the same manner as in Example 1, except that the coating slurry was prepared by adding 2.39 g of the acrylic polymer binder and 30 g of the inorganic particles, and no copolymer binder was used.

[0105] Comparative Example 5 A separation membrane was manufactured in the same manner as in Example 1, except that the coating slurry was prepared by adding 2.53 g of an acrylic polymer binder, 14.48 g of a copolymer binder, and 30 g of inorganic particles (the weight ratio of the acrylic polymer binder, the copolymer binder, the additives, and the inorganic particles was 3:5:3:89).

[0106] Comparative Example 6 A separation membrane was manufactured in the same manner as in Example 1, except that the coating slurry was prepared by adding 2.68 g of an acrylic polymer binder, 30.68 g of a copolymer binder, and 30 g of inorganic particles (the weight ratio of the acrylic polymer binder, the copolymer binder, the additives, and the inorganic particles was 3:10:3:84).

[0107] Comparative Example 7 A separation membrane was manufactured in the same manner as in Example 1, except that in the preparation of the coating slurry, only polyacrylic acid was used instead of the copolymer binder.

[0108] Comparative Example 8 A separator was manufactured in the same manner as in Example 1, except that in preparing the coating slurry, a copolymer binder obtained by polymerizing polyacrylic acid and polyacrylamide in a ratio of 3:7 was used.

[0109] Comparative Example 9 A separator was prepared in the same manner as in Example 1, except that in preparing the coating slurry, only polyacrylamide was used instead of the copolymer binder.

[0110] Experimental Example 1. Confirmation of the properties of the separation membrane depending on the properties of the copolymer binder The state of the separators prepared in Example 1 and Comparative Examples 1 to 3 was checked, and the properties of the separators according to the molecular weight of the copolymer binder used were checked. The properties are shown in Table 1 below.

[0111] In Comparative Examples 2 and 3, the viscosity of the coating slurry exceeded 1,000 cps, and coating using a bar coater was not possible. Hereinafter, the physical properties of the separators prepared according to Example 1 and Comparative Example 1 were examined.

[0112] Measurement of air permeability The air permeability was measured using a Gurley densometer (Gurley, 4110N) by measuring the diameter of 28.6 mm and the area of ​​645 mm for 100 cc of air.2 The time it took for the solution to permeate the separation membrane was measured. dry Confirmation of improvement in heat shrinkage rate under the condition Test pieces measuring 5 cm x 5 cm were prepared as the separators of the examples and comparative examples. The test pieces were stored in a 200°C convection oven for 30 minutes, and the thermal shrinkage in the MD (machine direction) and TD (transverse direction) directions was calculated by [(initial test piece length - @200 / length after storage for 0.5 hours) / (initial test piece length)] x 100(%).

[0113] Wet Confirmation of improvement in heat shrinkage rate under the condition Test pieces of 5 cm x 5 cm were prepared as the separators of the examples and comparative examples, and were inserted into aluminum pouches of 7 cm x 10 cm, respectively. 1 g of electrolyte was poured into the pouches, and the pouches were sealed.

[0114] The electrolyte used was a solvent in which ethylene carbonate (EC) / ethyl methyl carbonate (EMC) was mixed in a weight ratio of 3 / 7, and contained 3 mol of vinylene carbonate (VC), 1.5 mol of propane sulfone (PS), 1 mol of ethylene sulfate (ESa), and 1 mol of lithium salt LiPF6 as additives.

[0115] The sealed pouch was stored in a hot box at 135°C for 30 minutes, and then the thermal shrinkage in the MD and TD directions was calculated by [(initial test piece length - @135 / length after storage for 0.5 h) / (initial test piece length)] x 100 (%). Confirmation of EL wettability Test pieces measuring 5 cm x 5 cm were prepared as the separation membranes of the examples and comparative examples, and 2 μL of propylene carbonate (PC) was dropped onto the surface of the separation membrane as an electrolyte. The length of the droplet that spread in the MD and TD directions after 5 minutes was measured based on the droplet boundary surface immediately after the drop was dropped.

[0116] [Table 1] Experimental Example 2. Confirmation of membrane properties depending on copolymer binder content The state of the separators prepared according to Examples 2 to 3 and Comparative Examples 4 to 6 was examined, and the physical properties of the separators according to the content of the copolymer binder used were examined and are shown in Table 2 below.

[0117] In Comparative Examples 5 and 6, the viscosity of the coating slurry exceeded 1,000 cps, and coating using a bar coater was not possible. Hereinafter, the physical properties of the separators prepared according to Examples 2 and 3 and Comparative Example 4 were examined. The methods for examining each physical property were the same as those in the above-mentioned experimental examples.

[0118] [Table 2] Experimental Example 3. Confirmation of the physical properties of the separation membrane depending on the copolymerization ratio of the copolymer binder The physical properties of the separators prepared according to Examples 1 and 4 and Comparative Examples 7 to 9 were determined according to the copolymerization ratio of the copolymer binder used, and are shown in Table 3 below. The method for determining each physical property was the same as in the above-mentioned experimental examples.

[0119] [Table 3] Although the present invention has been described above with reference to the preferred embodiments, it will be understood by those skilled in the art or those having ordinary knowledge in the art that the present invention can be modified and changed in various ways without departing from the spirit and technical scope of the present invention as described in the claims below. Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.

Claims

1. The present invention includes a porous polymer substrate and a porous coating layer formed on at least one surface of the porous polymer substrate, The porous coating layer includes an acrylic polymer binder, a copolymer binder, and inorganic particles, The weight average molecular weight of the copolymer binder is 40,000 to 80,000; The copolymer binder and the inorganic particles are contained in a weight ratio of 1:93 to 1:

20.

2. The acrylic polymer binder is (Meth)acrylic acid, (meth)acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, n-ethylhexyl methacrylate, 2-ethylhexyl methacrylate 2. The separator for an electrochemical element according to claim 1, comprising at least one monomer selected from the group consisting of butyl (meth)acrylate, hydroxyethyl methacrylate, (meth)acrylonitrile butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-oxyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate, as a repeating unit. 。

3. The copolymer binder is 2. The separator for an electrochemical device according to claim 1, which is a copolymer of two or more selected from the group consisting of polyacrylic acid, polyacrylamide and polyvinyl alcohol.

4. The copolymer binder is 4. The separator for an electrochemical device according to claim 3, wherein polyacrylic acid and polyacrylamide are copolymerized in a ratio of 8:2 to 5:

5.

5. The acrylic polymer binder has a particle shape with an average particle size (D50) of 100 nm to 500 nm, The separator for an electrochemical device according to claim 1 , wherein the copolymer binder is in a non-particulate form.

6. The porous coating layer comprises:

2. The separator for an electrochemical device according to claim 1, wherein the inorganic particles are present in an amount of 90 to 95% by weight based on the total weight of the porous coating layer.

7. The separator for an electrochemical device according to claim 1 , wherein a content of the acrylic polymer binder is greater than a content of the copolymer binder, based on a weight of the porous coating layer.

8. 8. The separator for an electrochemical device according to claim 7, wherein the acrylic polymer binder and the copolymer binder are contained in a weight ratio of 5:1 to 1.5:

1.

9. An electrochemical device comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, An electrochemical element, wherein the separator is the separator for electrochemical elements according to claim 1 .

10. The electrochemical device of claim 9 , further comprising an electrolyte solution containing a solvent in which ethylene carbonate (EC) / ethylmethyl carbonate (EMC) are mixed at a weight ratio of 3 / 7.

Citation Information

Patent Citations

  • Coating starting material for secondary battery separator, coating material for secondary battery separator, secondary battery separator, method for producing secondary battery separator, and secondary battery

    WO2023276867A1